The Chiapas Rebellion : - Harvey, Neil (Duke University Press, 1998)
In 1994 the Zapatista rebellion brought international attention to the southern Mexican state of Chiapas. Neil Harvey combines ten years of field work in Chiapas with extensive historical and political research to provide a comprehensive history of conflict in this region and a nuanced analysis of this rural uprising against federal bureaucracy and landed elites.